A look at inclusive education in Brazil through the BDTD (Research, Society and Development, 2021)
This study aims to quantify the stricto sensu academic productions contained in the Brazilian Digital Library of Theses and Dissertations (BDTD) that address the theme Inclusive Education. The purpose of the survey was to elaborate an overview of the number of scientific productions on the subject in the last twenty years. To this end, this study used a bibliographic review, where a survey of stricto sensu productions was carried out on the BDTD website, using the descriptor Inclusive Education and Children, in quotation marks, with filters dissertations and theses in the period 2000 to 2020. The study registered a total of three hundred and fourteen scientific productions with this theme, with 235 researches classified in the academic Masters modality and 79 Doctoral theses. The data revealed that the year 2018 was the period that recorded the highest concentration of this theme with 36 insertions of research in the field, followed by the year 2017, which showed 31 occurrences. On average, this theme registered 15 publications per year of occurrence throughout the time series, demonstrating a large volume of Srito Sensu production on the subject in Brazil. The Universities that stood out the most in the productions on this theme were UNESP with 36 occurrences, followed by UFSCAR with 32 productions and PUC with 27 occurrences. The analysis pointed out that the regions that produced the most on the subject were the southeast region of the country and with the lowest index was the northeast region.